Security-Based Event-Triggered Fuzzy Control for Multiarea Power Systems Under Cross-Layer DoS Attacks - Li, Xiehuan; Ye, Dan (IEEE transactions on circuits and systems. I, Regular papers, 2023)
This paper addresses the fuzzy load frequency control (LFC) problem for nonlinear multiarea power systems subject to cross-layer denial-of-service (DoS) attacks and network resource constraints. A novel switched interval type-2 fuzzy power model with three modes is established to reflect the impact of cross-layer DoS attacks. Moreover, to save network resources, memory-based dynamic event-triggered mechanisms, whose threshold parameters and conditions fully utilize historical packets, are proposed. Then, the boundary information of multiple membership function samples combined with slack matrices is considered to facilitate stability analysis. Besides, the piecewise Lyapunov-Krasovskii functional approach is used to ensure the exponential stability of systems. Finally, the proposed resilient LFC strategy is demonstrated by three-area power systems.